A SUBSTANTIAL COMPONENT OF PROFESSION – ORIENTED FOREIGN LANGAGE TEACHING - Iskakova, R.; Tileuzhanova, K.T.; Kupeeva, Zh.S. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2015)
The article discusses the features of professional training-oriented communication in a foreign language of students of not language high schools.
Keywords: professional training; professional-oriented approach; cognitive-communication skills; authentic texts